Destroying sanctuary the crisis in human service delivery systems - Bloom, Sandra L., 1948-; Farragher, Brian J. (New York ; Oxford : Oxford University Press, 2011)
Describing what happens to human service delivery programs under the impact of unrelenting stress and multiple losses. Many social services of every size, shape, and variety are collapsing under over thirty years of system fragmentation even while public costs have escalated dramatically.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mental health services -- United States; Social service -- United States